A 7 Year Summary of Emergency Department Visits by Patients With Mental Health Disorders - Brathwaite, Danielle; Waller, Anna E.; Gaynes, Bradley N.; Stemerman, Rachel; Deselm, Tracy M.; Bischof, Jason J.; Tintinalli, Judith; Brice, Jane H.; Bush, Montika (Frontiers in Psychiatry, 2022)
Emergency departments (EDs) have been increasingly utilized over time for psychiatric care. While multiple studies have assessed these trends in nationally representative data, few have evaluated these trends in state-level data. This investigation seeks to understand the mental health-related ED burden in North Carolina (NC) by describing trends in ED visits associated with a mental health diagnosis (MHD) over time. Using data from NC DETECT, this investigation describes trends in NC ED visits from January 1, 2008 through December 31, 2014 by presence of a MHD code. A visit was classified by the first listed MHD ICD-9-CM code in the surveillance record and MHD codes were grouped into related categories for analysis. Visits were summarized by MHD status and by MHD category. Over 32 million ED visits were recorded from 2008-2014, of which 3,030,746 (9.4%) were MHD-related visits. The average age at presentation for MHD-related visits was 50 years (SD 23.5) and 63.9% of visits were from female patients. The proportion of ED visits with a MHD increased from 8.3% to 10.2% from 2008-2014. Annually and overall, the largest diagnostic category was stress/anxiety/depression. Hospital admissions resulting from MHD-related visits declined from 32.2% to 18.5% from 2008-2014 but remained consistently higher than the rate of admissions among non-MHD visits. Similar to national trends, the proportion of ED visits associated with a MHD in NC has increased over time. This indicates a need for continued surveillance, both stateside and nationally, in order to inform future efforts to mitigate the growing ED burden.